Modified orthogonal regression estimator in the quadratic errors-in-variables model - Repetatska, G. (Інститут математики НАН України, 2005)
The quadratic functional measurement error model with equal error variances is considered. The asymptotic bias of an orthogonal regression estimator is derived. A modiﬁed estimator which has smaller asymptotic bias for small measurement errors is presented.